The geometric model-based patient-specific simulations of turbulent aortic valve flows - Stupak, E.; Kačianauskas, R.; Kačeniauskas, A.; Starikovičius, V.; Maknickas, A.; Pacevič, R.; Staškūienė, M.; Davidavičius, G.; Aidietis, A. (Archives of Mechanics, 2017)
This paper presents the patient-specific simulations of the aortic valve based on the proposed geometric model. A structural analysis is performed by using the finite element method to determine the stress-strain state of the aortic valve. The study is focused on the investigation of various turbulence models crucial for the appropriate description of the flow in the deceleration phase, following the peak systole. A comparative study of the flow solution without a turbulence model and the numerical results obtained by using various turbulence models is also performed. The results yielded by the shear-stress transport k-ω model supplemented with the intermittency transition equation most closely match those of numerical simulations without a turbulence model.